DIARY OF A WIMPY KID DO-IT-YOUYSELF BOOK - JEFF KINNEY (PUFFIN New York, 2013)
A young boy and his Norwegian grandmother, who is an expert on witches, together foil a witch's plot to destroy the world's children by turning them into mice